The efficacy of fractional erbium:YAG laser (2940 nm) compared to Microneedling of topical amniotic membrane stem cell conditioned medium (AMSC-CM) for photoaging - Cita Rosita Sigit Prakoeswa; Riyana Noor Oktaviyanti; Wisnu Triadi Nugroho; Febrina D Pratiwi; Luh Mas Rusyati; I G A A Praharsini; I G A A Elis Indira (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Photoaging is a complex biologic process that affects various layers of the skin. Amnioticmembrane stem cell conditioned medium (AMSC-CM) that contain growth factors and have capability toimprove clinical picture of photoaged skin. Microneedling and laser devices are transdermal drug deliverymethods which shows promising results to improve photoaging .Objective: To investigate the efficacy of topical AMSC-CM after YAG erbium fractional laser compare tomicroneedling in photoaging.Method :A clinical study, 60 adult women with photoaging. Randomized into two groups A 30 womenreceived AMSC-CM after fractional erbium:YAG laser (2940nm) and group B 30 woman received AMSCCM after microneedling. Both groups received the treatment 3 times with 2 weeks interval. The improvementof pore, wrinkle, and UV spot as was evaluate before, after and post treatment using computer-stimulatedphotograph skin analyzer.Result: The evaluation of pore and UV spot showed greater improvement in the group of AMSC-CM withfractional erbium:YAG laser compare to AMSC-CM with microneedling group (pore p:0,00 and UV spotp:0,00). There was no significant different (p 0.43) of wrinkle improvement between both groups.Conclusion: The combination of AMSC-CM and fractional erbium:YAG laser have better efficacy in theimprovement in photoaged skins.